Fabrication and characterization of tungsten disulphide/silicon heterojunction photodetector for near infrared illumination - Ahmad, Harith; Rashid, Haroon; Ismail, Mohammad Faizal; Thambiratnam, Kavintheran (Elsevier, 2019)
Tungsten disulphide (WS 2 ), a member of the transition metal dichalcogenide (TMD) family that is known for its superior optoelectronic properties is used in this work to fabricate a low cost and highly efficient photodetector for operation in the near infrared (NIR) region. The WS 2 /Si heterojunction photodetector is fabricated using the drop cast method. Sample analysis shows Raman shifts at the E 1 2g and A 1g phonon modes located at 349.84 cm −1 and 419.62 cm −1 , validating the growth of monolayer 2H-WS 2 with a direct bandgap of 2.06 eV. Field emission scanning electron microscope (FESEM) analysis reveals an inhomogeneous surface on the film, while energy-dispersive X-ray (EDX) spectroscopy shows non-stoichiometric WS 2 layer growth on the Si wafer. Current-voltage (IV) measurements are performed in the NIR region with a 785 nm red laser source under dark and illuminated conditions. From the IV measurements, the threshold voltage is determined to be 2.2 V, and the photocurrent is found to be highly dependent on the laser power. The fabricated photodetector has a high responsivity of 10.46 mA/W and detectivity of 1.17 × 10 9 Jones for an incident light intensity of 11.696 mW.cm -2 . These results are promising as an alternative low-cost fabrication method with potential for the development of photovoltaic and optoelectronic applications. © 2019 Elsevier GmbH